If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = 2y + 8(y + 1) + 5(x + 5) Reorder the terms: 0 = 2y + 8(1 + y) + 5(x + 5) 0 = 2y + (1 * 8 + y * 8) + 5(x + 5) 0 = 2y + (8 + 8y) + 5(x + 5) Reorder the terms: 0 = 2y + 8 + 8y + 5(5 + x) 0 = 2y + 8 + 8y + (5 * 5 + x * 5) 0 = 2y + 8 + 8y + (25 + 5x) Reorder the terms: 0 = 8 + 25 + 5x + 2y + 8y Combine like terms: 8 + 25 = 33 0 = 33 + 5x + 2y + 8y Combine like terms: 2y + 8y = 10y 0 = 33 + 5x + 10y Solving 0 = 33 + 5x + 10y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 0 + -5x = 33 + 5x + -5x + 10y Remove the zero: -5x = 33 + 5x + -5x + 10y Combine like terms: 5x + -5x = 0 -5x = 33 + 0 + 10y -5x = 33 + 10y Divide each side by '-5'. x = -6.6 + -2y Simplifying x = -6.6 + -2y
| 4e+-3e+-2e=1+-9 | | Y=5x^3-17x^2-12x | | 23+24a=29+23a | | 5s-1-6s^2=0 | | 5a(3a-5)(5a-1)=0 | | -(2f-4)=-4-f+2 | | 3z+5+2z=13+3z | | =3(x+y)+4(y+x) | | 14+3n=8n-3+10x | | 2x^2+12+9x-18-3x-4x=0 | | x+x+1+x+2=-3.75 | | 11+3x-7=6x+-3x | | 9w-18w-18w+36= | | =6+6(x+4)+15y+x | | -1(x+4)+5=4x+1-5x | | 14+4x+6=8x | | -19x+23y=-3 | | 3x+14x+2=19 | | -4p+15=-15 | | =5(x+3)+3(y+1) | | 5x-3(x-4)=-5+4x+13 | | (x+8)(x-7)=16 | | 0=-16t^2+20t+40 | | -4w-4= | | 99-4s-6s=-9 | | 9=b | | y=xcos(x) | | 2+2=8b | | 2x-5(x-5)=-4+3x+17 | | =2(x+y)+9x+6y | | 42=3(2-6h) | | z+8(z-4)=-4 |